Peran Pembaruan Teknologi Dalam Mengoptimalkan Efisiensi Operasional Di Bidang Manajemen Ekonomi: Tinjauan Kritis Literatur - Edison Siregar; Arsidin Batubara; Fakhrurrozi; Imelda Mathauli Pardede (Yayasan Perguruan Kampus, 2025)
In the era of the digital economy, technological innovation plays an important role in improving the operational efficiency of companies. This is especially relevant in economic management, where technologies such as automation, artificial intelligence (AI), big data analytics, and cloud computing can boost productivity, accelerate decision-making, and optimize resource allocation. This study aims to analyze the role of these technologies in economic management through a systematic literature review of research published in the last five years. Data searches were conducted through international journal databases such as ScienceDirect, SpringerLink, and IEEE Xplore, which include articles related to automation, AI, big data analytics, and cloud computing. The results of the study show that the appropriate application of technology can increase efficiency, reduce costs, and provide competitive advantages for companies. However, the application of this technology also requires significant investment and organizational readiness, both in infrastructure and technical skills of the workforce. The implications of the results of this study indicate that the application of technological innovation is an urgent need for companies to remain relevant in an increasingly competitive market, but also requires an adaptive human resource development strategy. These findings contribute to the understanding of the role of technology in economic management and the importance of organizational readiness in its application.